Ecological Risk Assessment of Heavy Metals is Surface Mangrove Sediments Collected The Sepang River Estuary, Peninsular Malaysia - Yap, Chee Kong; Chelvan, Nirmal Kumar; Wong, Koe Wei (Nova Science Publishers, 2018)
Sepang Besar River (SBR) and Sepang Kecil River (SKR) were previously known as piggery farming areas in the early 1990s. These rivers are known to be highly contaminated with Zn and Cu as they received effluents from the piggery farming. Besides that, domestic wastes, boating and fish farming effluents were also common in these rivers banks. In this study, the surface sediments collected form SBR and SKR in 2007 were analysed for its Cd, cu, Fe, Ni, Pb and Zn concentrations. The present study revealed